A learning organization in the service of knowledge management among nurses: A case study. Issue 5 (October 2015) - Gagnon, Marie-Pierre; Payne-Gagnon, Julie; Fortin, Jean-Paul; Paré, Guy; Côté, José; Courcy, François
Highlights Learning organizations are seen as a promising avenue for knowledge management. We investigated the effects of a learning organization on nurse practice. It influenced professional development, knowledge management and quality of care. Its effect on nurse retention and work of other health professionals was limited.